ANALISIS HUBUNGAN ARUS KAS DENGAN HARGA SAHAM PADA PERUSAHAAN YANG TERGABUNG DALAM KELOMPOK LQ 45 DI BURSA EFEK INDONESIA PERIODE 2007 - 2008 - Y. Yuliusman (Universitas Trunojoyo Madura, 2009)
This research has purpose: (1) To know operation cash flowcorelation, investment cash flow, and funding cash flow in parsial to stockprice at LQ 45 which listed in BEI periode 2007-2008. (2) To knowoperation cash flow corelation, investment cash flow, and funding cashflow in simultan to stock price at LQ 45 company which listed in BEIperiode 2007-2008. (2) To know which of which more corelational operationcash flow, investment cash flow and funding cash flow to stock price atLQ 45 company which listed in BEI periode 2007-2008.The hypotheses was operation cash flow, investment cash flow, andfunding cash flow has corelational in simultan and parsial to stock priceat LQ 45 company. Based on result of multiple corelational in simultanoperation cash flow, investment cash flow and funding cash flow hassignificant corelational to stock price. Level of free variables corelationalto stock price in simultan is 27,5%. Parsially, investment cash flow andfunding cash flow that is not had an corelation on in significant stockprice and operating cash flow has corelational that is very significant tostock price